HUBUNGAN PERAWATAN CATHETER VENA CENTRAL (CVC) TERHADAP TERJADINYA INFEKSI ALIRAN DARAH PRIMER (IADP) - Basri, Basri (Universitas Prima Indonesia, 2020)
Central vein Catheter Treatment (CVC) is the treatment of a hose that is used to provide liquids or medicines. Appliance is installed in a blood vessel near the heart. The primary infection of blood flow occurring within 48 hours after the installation of CVC The purpose of this research is to know the CVC treatment relationship in CVC attached patients to the primary blood flow infection in ICU RSUP. H. Adam Malik Medan. The study uses correlation and observation research methods. The population in this research is the entire patient who CVC has installed, as well as all the nurses who do the CVC treatment. Based on the data obtained by the patient as much as 76 people. Patients are inclusiveness if the patient is hospitalized in less than 24 hours, and drop out if the patient dies in the treatment before it is found signs of IADP,as well as patients who come out of Adam Malik, then there are 32 patients. Research instruments in the form of questionnaires according to IADP. Analysis of data used statistical tests test Chi-Square. The results of the majority of the study of a major vein catether treatment (CVC) were as much as 28 (87.5%), the majority of which did not occur as much as 27 people (84.4%). Statistical test results obtained by the value of p- value =0.000 (<0.05) can be concluded there is a central venous catether treatment Relationship (CVC) in patients attached CVC to the occurrence of primary blood flow infection).